2016
DOI: 10.1017/s2040174416000386
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and early-life predictors of atopy and allergic disease in Canadian children: results of the Family Atherosclerosis Monitoring In earLY life (FAMILY) Study

Abstract: Prenatal and early-life environmental exposures play a key role in the development of atopy and allergic disease. The Family Atherosclerosis Monitoring In earLY life Study is a general, population-based Canadian birth cohort that prospectively evaluated prenatal and early-life traits and their association with atopy and/or allergic disease. The study population included 901 babies, 857 mothers and 530 fathers. Prenatal and postnatal risk factors were evaluated through questionnaires collected during the antena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
(49 reference statements)
1
26
1
Order By: Relevance
“…Roduit et al found that children with prenatal pet and cat contact had a lower risk of AD in the first 2 years of life than those without (10). Another study regarding prenatal maternal exposure to dogs at home was "protective" against allergic diseases (27). Similarly, the risk of AD was also lower in the group of pet ownership during pregnancy in this study although it did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Roduit et al found that children with prenatal pet and cat contact had a lower risk of AD in the first 2 years of life than those without (10). Another study regarding prenatal maternal exposure to dogs at home was "protective" against allergic diseases (27). Similarly, the risk of AD was also lower in the group of pet ownership during pregnancy in this study although it did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 53%
“…It is reported that pet-or dog-ownership during pregnancy significantly lowered the risk of AD in the year of 1 or 2 in two previous prospective birth cohort studies (10,27). Roduit et al found that children with prenatal pet and cat contact had a lower risk of AD in the first 2 years of life than those without (10).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a study by Amberbir et al, 36 in a cohort of infants in Ethiopia, linked acetaminophen use in the first 3 years of life with increased incidence of wheeze and eczema between ages 3 and 5 years. In contrast, a recent cross-sectional study of Canadian infants, by Batool et al, 37 found that acetaminophen exposure was inversely associated with allergic disease (defined as parental report of any of the following: wheezing, eczema, allergic rhinitis, or food allergy).…”
Section: Discussionmentioning
confidence: 87%
“…5 One 2016 study conducted in Ontario found that 44% of toddlers suffered from food allergies, environmental allergies (wheezing, asthma, eczema or rhinitis), atopy or a combination thereof. 6 Though one cross-sectional and several longitudinal studies have assessed the early-life programming of allergic diseases by maternal weight or GWG, they have been limited by small sample sizes (<1000) 7 8 and self-reported measures of the exposure or outcome, [7][8][9][10][11][12][13][14][15][16][17][18][19] which have reduced their generalisability and validity. Further, most have focused on asthma alone, [7][8][9][10][11][12][13][14] none have examined anaphylaxis and none have calculated risk by the length of follow-up time, opting instead for aggregate rates (loglinear model), 8 13 17 odds (logistic model) 7 9-12 14- 16 18 or prevalence ratios (log-binomial model).…”
Section: What This Study Hopes To Add?mentioning
confidence: 99%